Artificial Intelligence in Education: Analysis of Advantages and Risks (Uzbekistan Open Conference, 2025)
In today’s world, artificial intelligence is developing rapidly, as advanced countries and corporations are investing heavily in this field. This opens up new opportunities for education but also creates serious challenges. In this article, I examine the practical advantages and disadvantages of implementing AI in the current environment. On the one hand, I analyze such benefits as personalized learning and the automation of routine tasks. On the other hand, I explore real problems, ranging from the risk of declining critical thinking to issues of academic integrity. Particular attention is paid to the prospects for further implementation of AI in education and the conditions that will allow its potential to be used as effectively and safely as possible.